Estudo do potencial migratório de células tumorais prostáticas expostas à fibronectina - Souza, Greyce Roberta de [UNESP] (2015)
The prostate is a gland attached to the male genital system, found only in mammals, whose main function is to produce part of the seminal fluid. Prostatic lesions appear most commonly in middle-aged men and prostate cancer (PCa) is the most commonly cancer diagnosed and the second leading cause of cancer deaths among men in America and in Western European countries. The extracellular microenvironment is a complex network comprising extracellular matrix (ECM) and regulatory molecules. The ECM has a fundamental role in the regulation of many cellular events, such as adhesion, proliferation, differentiation, among others. A fine balance is maintained between the synthesis and degeneration of its components, and when unregulated can cause tissue damage and cancer. In the prostate, the interactions between the epithelial tissue and its stroma are responsible for maintaining normal physiological function through proliferative and migratory restrictions. When cancer develops, transformed cells lose these restrictions, while the stroma is adapted to support the function of the tumor. It is known that tumor cells with invasive potential acquire migratory phenotype associated with increased expression of genes involved in cell motility, allowing these cells to respond to signals from the tumor microenvironment. Thus, our study aimed to study the action of fibronectin, an ECM adhesion molecule, on migration of prostate cancer cells and the expression of molecules involved in this process. To achieve this goal, we performed the exposure of LNCaP and PC-3 cells to fibronectin in the concentration of 25 mg / mL and analyzed cell viability, morphology, total number of nucleoli, location and activity of matrix metalloproteinases -2 and -9 and the process of cell migration. Exposure to fibronectin did not alter cell viability and morphology, but increased the amount of nucleoli, as well as marking and the activity of MMP -2 and -9 and decreased migration...